Thin hydroxyapatite coating on AZ91D magnesium alloy fabricated via RF-magnetron sputtering. Issue 1 (October 2015) - Mukhametkaliyev, T M; Surmeneva, M A; Mueller, M; Prymak, O; Epple, M; Surmenev, R A
Abstract: In this study the morphology, composition, structure and wettability of radiofrequency (RF) magnetron sputter-deposited hydroxyapatite (HA) coating deposited on the surface of AZ91D magnesium alloy were investigated. The results revealed that the fabricated coating is uniform, homogeneous with the structure of the stoichiometric HA. The deposition of the HA coating did not change significantly the surface wettability of the bare alloy, however water contact angle dynamics in the case of the HA coated substrates revealed a lower rate of a droplet spreading over the surface.